ANALISIS FAKTOR KEUNGGULAN KOMPETITIF INDUSTRI KREATIF SONGKET SILUNGKANG SAWAHLUNTO - LARAS LONIKA; Rahmanelli Rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This study aims to analyze the competitive advantage factors of the Silungkang Sawahlunto songket creative industry. This type of research is quantitative descriptive. The data used are primary data obtained from observations, surveys and questionnaires. The sampling technique used purposive sampling with a population of all industrial household owners in Tigo Village, using a selection table from Isac Michcael, Silungkang District and a total sample of 88 respondents. The data analysis technique used in this study is the percentage analysis. The results showed a factor of competitive advantage 1.) based on human resources according to the level of education and has long been owned by industry owners by pursuing as craftsmen, songket, industrial households supported by women (76.1%), with junior high school education levels ( 45%)), the industry has been around for more than 15 years (43.2%). 2) Analysis of competitive advantage factors based on physical resources related to large capital and capital sources, where large capital can increase the amount of productivity so as to increase marketing will be broader.3) seen from the results of the marketing distribution of Silungkang songket generally around Sawahlunto to Padang, Bukiktinggi, and Solok.